Extraction of omega 3 fatty acids from sardine byproducts using supercritical carbon dioxide - Sahena, Ferdosh; Sarker, Md. Zaidul Islam; Yunus, Kamaruzzaman; M., Abir H.; A. H., Rukshana (2016)
Sardine generally processed as canned fish, and in consequence of a lot of solid wastes are generated as by-products which could be good sources of fish oil. Omega-3 fatty acid compositions of total lipids extracted by supercritical carbon dioxide (SC-CO2) from sardine fish by-product (head, skin and viscera) were determined and the results were compared with Soxhlet extraction. SC-CO2 extraction was performed at optimized condition at a temperature of 60 0C, the pressure of 35 Mpa and flow rate of 3 ml min-1. Highest yield were obtained from the skin (42.5%) followed by the head (22.4%) and the viscera (9.6%) which is closer to that of the yield of Soxhlet extraction method where 44%, 23% and 11% (on dry basis) oil were yielded from skin, head and viscera, respectively. Saturated fatty acid was dominant in corporate with monounsaturated and polyunsaturated fatty acid in all organs and the difference of extracted fatty acids between SC-CO2 and Soxhlet methods were non-significant. Docosahexaenoic acid (DHA) was characteristically major PUFA accounting 19.8% in head, 15.4% in skin and 13.6% in viscera of the total fatty acids. Total oil extracted by SC-CO2 had lower free fatty acid content than the oil extracted by Soxhlet method. Thus, SC-CO2 could be the effective method for extracting omega-3 PUFA rich fish oil from sardine by-products.